2014
DOI: 10.1016/j.surfcoat.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of yttria-stabilized zirconia thin films by high power impulse magnetron sputtering and pulsed magnetron sputtering

Abstract: Yttria-stabilized zirconia (YSZ) thin films were reactively sputter-deposited by high power impulse magnetron sputtering (HiPIMS) and pulsed direct current magnetron sputtering (DCMS). The use of substrate bias voltage was studied in both modes of deposition as a process parameter to promote the growth of dense and less columnar films. Films were deposited on both Si(100) and NiO-YSZ fuel cell anodes. The texture, morphology and composition of the deposited films were investigated with regard to their applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Widely practiced for compound films, including nitrides [77,199,[291][292][293], carbides [294], oxides [277,[295][296][297][298][299][300][301][302], and more complex compounds [303,304]. [306].…”
Section: Deposition In Vacuummentioning
confidence: 99%
“…Widely practiced for compound films, including nitrides [77,199,[291][292][293], carbides [294], oxides [277,[295][296][297][298][299][300][301][302], and more complex compounds [303,304]. [306].…”
Section: Deposition In Vacuummentioning
confidence: 99%
“…Typically, to make a thin film electrolyte on the sub‐micrometer scale, different solution‐based processes like metal‐organic deposition and spray pyrolysis , chemical and physical , vapor deposition methods are used. The solution‐based processes have problems associated with shrinkage that accompanies drying and sintering.…”
Section: Introductionmentioning
confidence: 99%
“…The largest size of single cells with the magnetron sputtered electrolyte, known from literature, is 5 × 5 cm 2 , . This cell's size is obviously insufficient for the manufacture and testing of SOFS stacks.…”
Section: Introductionmentioning
confidence: 99%
“…Most often to deposit YSZ electrolyte, sputtering in DC-pulsed mode is used. However, in the works of Sonderby et al [37,38], for depositing the YSZ electrolyte on NiO/YSZ anodes, high power impulse magnetron sputtering was used. HiPIMS utilizes extremely high power densities of the order of kW/cm 2 in short pulses of tens of microseconds at low duty cycle (on/off time ratio) of <10%.…”
Section: Magnetron Sputtering Of Ysz Electrolyte Effect Of Depositiomentioning
confidence: 99%
“…Sonderby et al [37] compared the microstructure of YSZ electrolytes deposited on (5 × 5) cm 2 anode substrates by the DC-pulsed magnetron sputtering and HiPIMS methods at a bias voltage in the range of 0 to -75 V. It was concluded that in the case of DC-pulsed magnetron sputtering, an increase in the bias voltage does not lead to complete suppression of the columnar structure of the electrolyte, whereas at high power impulse magnetron sputtering with a bias voltage of -50 V the dense electrolyte films without a columnar structure are deposited ( Figure 3). The electrochemical characteristics of SOFC have not been studied in this work.…”
Section: Magnetron Sputtering Of Ysz Electrolyte Effect Of Depositiomentioning
confidence: 99%